Smart Economy As Feature of Smart Planning Concept, Methodology and Application - وليد صيداوي; حسان عيسى (Latakia University Journal -Engineering Sciences Series, 2023)
The final developments in economics show its close connection to development in communication technology and information, and its links with Regional sciences also expanded. The planning have adopted, in a lot of countries, complete planning structures to connect between the different economic, urban and social sectors to achieve an integrated spatial development. The research poses the problem of the gap in the Economics development in the local reality and presents the smart economy, which is one of the characteristics of smart planning. as a solution that contributes to change the course of development planning to achieve integrated developments, and by introducing the concept of smart economics and clarifying its most important features to reach conclusions that contribute to clarify the future of local development.